Implementation of Universal Design For Learning (UDL) in Digital Learning Media: A Systematic Review - Zakariyah, M Fahmi; Yulianingsih, Wiwin; Hidayah, Lailatul Nur; Anisa, Anisa (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
This study explores the implementation of Universal Design for Learning (UDL) in digital learning media within the context of non-formal education to enhance accessibility, student engagement, and expression. Using a systematic literature review method, this research analyzes 17 articles from reputable journals to examine how various digital media formats such as text, audio, video, interactive graphics, and augmented reality (AR) can be effectively integrated to support UDL-based learning. The findings indicate that UDL-based digital learning media can address the diverse needs of learners through flexible content representation, active engagement strategies, and personalized learning pathways. However, challenges such as limited educator training, technological constraints, and infrastructure barriers remain significant obstacles to effective implementation. This study contributes to the field by synthesizing prior research to develop a comprehensive framework for optimizing UDL application in digital learning environments, particularly in non-formal education. The findings highlight the crucial role of collaboration among educators, technology developers, and policymakers in ensuring the scalability and sustainability of UDL-based digital learning initiatives. Furthermore, recommendations are provided to enhance educator training programs, infrastructure development, and data-driven approaches to support inclusive and adaptive digital education.